Red emission generation through highly efficient energy transfer from Ce3+ to Mn2+ in CaO for warm white LEDs. Issue 4 (18th December 2015) - Feng, Leyu; Hao, Zhendong; Zhang, Xia; Zhang, Liangliang; Pan, Guohui; Luo, Yongshi; Zhang, Ligong; Zhao, Haifeng; Zhang, Jiahua
Abstract : Red emission generation and application through efficient energy transfer from Ce 3+ to Mn 2+ in CaO. Abstract : CaO:Ce 3+, Mn 2+ phosphors with various Mn 2+ concentrations were synthesized by a solid state reaction method. Efficient energy transfer from Ce 3+ to Mn 2+ was observed and it allows the emission color of CaO:Ce 3+, Mn 2+ to be continuously tuned from yellow (contributed by Ce 3+ ) to red (by Mn 2+ ) with an increase in Mn 2+ concentration and upon blue light excitation. The red emission becomes dominant when the Mn 2+ concentration is ≥0.014 with an energy transfer efficiency higher than 87% which can reach as high as 94% for a Mn 2+ concentration of only 0.02. A critical distance of 10.5 Å for the Ce 3+ –Mn 2+ energy transfer was determined. A faster decrease of Ce 3+ luminescence intensity in comparison with its lifetime was observed on increasing the Mn 2+ concentration. The analysis of this feature reveals that the Ce 3+ excitation energy can be completely transferred to Mn 2+ if the Ce 3+ –Mn 2+ distance is shorter than 7.6 Å. A warm white LED was fabricated through integrating an InGaN blue LED chip and a blend of two phosphors (YAG:Ce 3+ yellow phosphor and CaO:0.007Ce 3+, 0.014Mn 2+ red phosphor) into a single package, which has CIE chromaticity coordinates of ( x = 0.37, y = 0.35), a correlated color temperature of 3973 K and a color rendering index of 83.1. The results indicate that CaO:Ce 3+, Mn 2+ may serve as a potential red phosphor for blue LED based warm white LEDs.